2023
DOI: 10.7150/ijms.77792
|View full text |Cite
|
Sign up to set email alerts
|

Post-Intensive Care Unit Multidisciplinary Approach in Patients with Severe Bilateral SARS-CoV-2 Pneumonia

Abstract: Background: Short and long-term sequelae after admission to the intensive care unit (ICU) for coronavirus disease 2019 are to be expected, which makes multidisciplinary care key in the support of physical and cognitive recovery. Objective: To describe, from a multidisciplinary perspective, the sequelae one month after hospital discharge among patients who required ICU admission for severe COVID-19 pneumonia. Design: Prospective cohort study. Environment: Multidisciplinary outpatient clinic. Population: Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…As previously observed, comparing with other causes of pneumonia, it can be inferred that COVID-19 pneumonia has a lower late mortality rate among ICU survivors [ 24 ]. The cause behind reduced long-term mortality rates for COVID patients remains unclear, as the incidence of pulmonary anatomical abnormalities and compromised physiological function is significantly high among individuals diagnosed with ARDS as a consequence of COVID-19 [ 6 ]. Additionally, research findings indicate that COVID-19 patients necessitating MV exhibit heightened levels of inflammatory markers, multiple organ dysfunction, and increased rates of in-hospital mortality [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously observed, comparing with other causes of pneumonia, it can be inferred that COVID-19 pneumonia has a lower late mortality rate among ICU survivors [ 24 ]. The cause behind reduced long-term mortality rates for COVID patients remains unclear, as the incidence of pulmonary anatomical abnormalities and compromised physiological function is significantly high among individuals diagnosed with ARDS as a consequence of COVID-19 [ 6 ]. Additionally, research findings indicate that COVID-19 patients necessitating MV exhibit heightened levels of inflammatory markers, multiple organ dysfunction, and increased rates of in-hospital mortality [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the understanding and evidence concerning long-term outcomes in individuals who required critical care due to COVID-19 diagnosis are currently limited. A prospective cohort study conducted in Spain in 2021, evaluating the sequelae occurred at the first month after hospital discharge among patients who required ICU admission for severe COVID-19 pneumonia, concluded that these patients need a long-term follow-up due to its expected bad prognosis, and this should be extended beyond 30 days after ICU discharge [ 6 ]. However, evidence regarding the optimal duration for follow-up care in individuals who have survived COVID-19 after being admitted to the ICU is still lacking [ 7 ].…”
Section: Introductionmentioning
confidence: 99%